Common value auctions with return policies - Ruqu Wang; Jun Zhang (Queen's University, Department of Economics, 2010)
This paper examines the role of return policies in common value auctions. We first characterize the unique symmetric equilibrium in first-price and second-price auctions with continuous signals and discrete common values when certain return policies are provided. We then examine how the return policies affect a seller's revenue. When the lowest common value is zero, a more generous return policy generates a higher seller's revenue; the full refund policy extracts all the surplus and therefore implements the optimal selling mechanism; given any return policy, a second-price auction generates a higher revenue than a first-price auction. In a second-price auction where the lowest common value is not zero but still smaller than the seller's reservation value, then a more generous return policy also generates a higher revenue; otherwise, the optimal return policy could be a full refund, no refund or partial refund policy.
Keywords: D44; D72; D82; 330; auctions; return policies; refund